1985
DOI: 10.1192/bjp.147.4.389
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Desipramine upon Melatonin and Cortisol Secretion in Depressed and Normal Subjects

Abstract: Melatonin and cortisol values in plasma were measured hourly over 24 hours in six depressed patients and six normal volunteers before treatment and after one and three weeks of treatment with desipramine. The normal volunteers were further tested one week after withdrawal of desipramine. The mydriatic effects of tyramine and phenylephrine eye drops were also recorded in the normal volunteers. In neither group of subjects did desipramine treatment reduce melatonin secretion, suggesting that functionally signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 19 publications
(13 reference statements)
1
34
0
Order By: Relevance
“…Frazer et al (1986) found no significant change in plasma melatonin concentrations in seven patients after 4 weeks treatment with desipramine, but no information is provided regarding clinical outcome. In one other study, plasma melatonin concentrations did not change following treatment with desipramine in seven patients (Thompson et al 1985). The authors do not describe the treatment outcome, but report relatively low mean plasma concentrations of desipramine (i.e., 70 Ϯ 9 ng/ml), which suggests a lower likelihood of clinical response.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Frazer et al (1986) found no significant change in plasma melatonin concentrations in seven patients after 4 weeks treatment with desipramine, but no information is provided regarding clinical outcome. In one other study, plasma melatonin concentrations did not change following treatment with desipramine in seven patients (Thompson et al 1985). The authors do not describe the treatment outcome, but report relatively low mean plasma concentrations of desipramine (i.e., 70 Ϯ 9 ng/ml), which suggests a lower likelihood of clinical response.…”
Section: Discussionmentioning
confidence: 87%
“…Jarrett et al (1988) found that acute, subtherapeutic doses of imipramine (e.g., 50 mg) did not increase nocturnal melatonin secretion in depressed patients, so that simple exposure to antidepressant is insufficient to enhance pineal activity in depressed subjects. Thompson et al (1985) reported that plasma melatonin concentrations increased in depressed patients after 3 weeks of desipramine treatment, but not after 1 week. This supports the hypothesis that increased melatonin output is linked to clinical response, which usually does not occur within 1 week, but often after 3 weeks of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Pharmac.,26,[753][754][755][756][757][758][759] Melatonin and cortisol increase after fluvoxamine Studies on melatonin levels in the plasma of depressed patients have attracted attention since they may indicate changes in circadian rhythms and reflect the influence of different lighting conditions in several forms of affective disorders (Wirz-Justice et al, 1979). At present a few studies have been published on the effect of antidepressant drugs on melatonin plasma levels in man indicating an enhancement of nocturnal melatonin secretions in depressed patients but not in normal subjects following 3 weeks desipramine treatment (Thompson et al, 1985) and increased concentrations at night and during the day after chronic clorgyline administration (Murphy et al, 1985). Recently, we observed that a 150 mg dose of the selective serotonin (5-HT) reuptake inhibitor and antidepressant drug fluvoxamine (FL) given at night to a group of healthy volunteers leads to a significantly increased early morning plasma level of melatonin.…”
mentioning
confidence: 99%
“…Depressed patients display altered melatonin release and abnormal melatonin levels (Rubin et al, 1992;Wetterberg, 1999), particularly in the acute phase of depressive illness (Srinivasan et al, 2006). Antidepressant therapy increases melatonin (Srinivasan et al, 2006;Thompson et al, 1985). Of note, a pilot study that looked at the use of melatonin in addition to cortisol as a prognostic marker for depression found promising results (Buckley & Schatzberg, 2010).…”
Section: Sleep and Circadian Rhythmmentioning
confidence: 99%